Application of Data Processing for Zakat Payments at Nur Salam Mosque Batik, Talaud Islands Regency - Jeling Kalase; Eliyah Acantha Manapa Sampetoding; Ikbal Tawinseet; Esther Sanda Manapa (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Zakat is to set aside a portion of the property owned if it is sufficient for the nisab and give it to those who are entitled to receive it. The process of working on a plan or completion of certain work such as zakat payment data still uses the manual method, this causes the data to be less effective. Therefore we need a computer-based data processing application that can handle and process data related to zakat as a whole quickly and accurately and can avoid errors in processing zakat payment data. The goal to be achieved by the author is to be able to provide solutions to problems that occur related to processing zakat payment data at the Nur Salam Bantik Mosque, as well as facilitating report generation. The application made is an application for processing zakat payment data at the Nur Salam Bantik Mosque using Visual Basic 6.0 programming language and Microsoft Access as a data base processor.